2002
DOI: 10.1029/2002gl015633
|View full text |Cite
|
Sign up to set email alerts
|

Estimating tidally driven mixing in the deep ocean

Abstract: [1] Using a parameterization for internal wave energy flux in a hydrodynamic model for the tides, we estimate the global distribution of tidal energy available for enhanced turbulent mixing. A relation for the diffusivity of vertical mixing is formulated for regions where internal tides dissipate their energy as turbulence. We assume that 30 ± 10% of the internal tide energy flux dissipates as turbulence near the site of generation, consistent with an estimate based on microstructure observations from a mid-oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
316
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(333 citation statements)
references
References 20 publications
15
316
1
1
Order By: Relevance
“…Concentrating intense mixing above rough topography where major tidal energy dissipates was found to be preferable for representing deep ocean stratification and Southern Ocean heat uptake in climate models (Saenko, 2006;Exarchou et al, 2013). The model sensitivity study by Jayne (2009) shows that using the tidal mixing parametrization proposed by St Laurent et al (2002) can significantly enhance the deep cell of the meridional overturning circulation (MOC) in comparison with only using an ad hoc background vertical diffusivity, although the upper cell of the MOC and the poleward heat transport (the often used diagnostics for adjudging climate models) are not strongly affected by this parametrization. Present climate and earth system models tend to use the St Laurent et al (2002) parametrization instead of the Bryan and Lewis (1979) type of background diffusivity (e.g.…”
Section: Diapycnal Mixing Associated With Internal Wave Energy Dissipmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrating intense mixing above rough topography where major tidal energy dissipates was found to be preferable for representing deep ocean stratification and Southern Ocean heat uptake in climate models (Saenko, 2006;Exarchou et al, 2013). The model sensitivity study by Jayne (2009) shows that using the tidal mixing parametrization proposed by St Laurent et al (2002) can significantly enhance the deep cell of the meridional overturning circulation (MOC) in comparison with only using an ad hoc background vertical diffusivity, although the upper cell of the MOC and the poleward heat transport (the often used diagnostics for adjudging climate models) are not strongly affected by this parametrization. Present climate and earth system models tend to use the St Laurent et al (2002) parametrization instead of the Bryan and Lewis (1979) type of background diffusivity (e.g.…”
Section: Diapycnal Mixing Associated With Internal Wave Energy Dissipmentioning
confidence: 99%
“…Improved understanding of mixing processes in the ocean has led to a parametrization of abyssal mixing induced by internal wave breaking associated with baroclinic tidal energy (St Laurent et al, 2002;Simmons et al, 2004). Concentrating intense mixing above rough topography where major tidal energy dissipates was found to be preferable for representing deep ocean stratification and Southern Ocean heat uptake in climate models (Saenko, 2006;Exarchou et al, 2013).…”
Section: Diapycnal Mixing Associated With Internal Wave Energy Dissipmentioning
confidence: 99%
“…In these areas, turbulent mixing has been inferred to be 100-1000 times larger than that of the ocean interior. Laurent et al [42] estimated the tidal mixing magnitude around steep bottom is nearly O(10 3 m 2 s 1 ). Tian et al [43] showed that diapycnal diffusivity in the SCS and the Luzon Strait is elevated by two orders of magnitude over that of the smooth bathymetry in the North Pacific, which has a typical background value of an open ocean.…”
Section: The Effects Of Vertical Mixing On Mocmentioning
confidence: 99%
“…TPX08 at 1/30 • (Egbert and Erofeeva, 2002). The parameterisations should include benthic and under-ice mixing (Luneva et al, 2015), and mixing by baroclinic tides (St. Laurent et al, 2002). Simmons et al (2004) consider the application of an internal tide energy flux parameterisation, driven by a barotropic tidal model (St. Laurent et al, 2002;Jayne and St. Laurent, 2001), and how to translate this to an interior vertical diffusivity for implementation in a coarse-resolution ocean circulation model.…”
Section: Tidesmentioning
confidence: 99%
“…The parameterisations should include benthic and under-ice mixing (Luneva et al, 2015), and mixing by baroclinic tides (St. Laurent et al, 2002). Simmons et al (2004) consider the application of an internal tide energy flux parameterisation, driven by a barotropic tidal model (St. Laurent et al, 2002;Jayne and St. Laurent, 2001), and how to translate this to an interior vertical diffusivity for implementation in a coarse-resolution ocean circulation model. In contrast, Allen et al (2010) explore using a 1-D mixing model (GOTM) driven at each horizontal grid cell by imposed sea-surface slopes to estimate the vertical profiles of tidal shear.…”
Section: Tidesmentioning
confidence: 99%